HOUSING SATISFACTION INDICATORS IN INDONESIA, ANALYSIS OF SPTK 2017 - Fahrizal Fahrizal; Ni Made Sukartini (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2020)
The issue of housing regarding livable homes is one indicator in the 11th Sustainable Development Goals (SDGs). At present, the limitations of the unliveable houses database and the lack of information regarding the housing satisfaction determinants cause housing problem in Indonesia. The studies of housing satisfaction determinant are still rarely found in Indonesia. Therefore, this study aims to obtain individual satisfaction indicators of the house's quality. This study uses the latest housing satisfaction microdata of Survei Pengukuran Tingkat Kebahagiaan (SPTK) 2017. The data is analysed with a logit model to obtain determinants of housing satisfaction. Estimation results show that women tend to feel more satisfied than men. Likewise, someone who lives in an urban tends to be more confident than someone who lives in a rural. Risen satisfaction of housing conditions is directly proportional to growing age, increased education and income. Homeownership status, livable homes, area of the house, as well as mastery of life support facilities such as vehicles, computer electronics, audio or visual electronics, and electronic communication devices increase the chances of housing satisfaction. Besides, we found different results related to marriage. Supplementing life support tools in analysis build marriage shifts insignificant.